Characterization of an intronless collagen gene family in the marine sponge Microciona prolifera. - Aho, S (1993)
Two independent clones from the genomic DNA of a marine sponge Microciona prolifera were isolated by hybridization to the Caenorhabditis elegans Col-1 gene and one clone was obtained from genomic DNA by PCR. They contain open reading frames (MpCol1, MpCol2, MpCol3, MpCol4) capable of coding for a family of collagens different from those previously found in sponges. Southern blotting of genomic DNA suggested the presence of several other homologous genes. cDNA clones covering most of the triple-helical coding domain and the 3' untranslated region of MpCol1 were isolated by specific primers and reverse PCR. Two cDNA clones end in the middle of an AATAAA sequence 170 bp downstream from the translation stop codon of MpCol1. The putative NH2-terminal noncollagenous peptide is composed of only seven amino acid residues. The 1074-bp triple-helical coding region is not interrupted by intervening sequences. It codes for a polypeptide of 120 Gly-Xaa-Yaa triplets with only one short interruption near the COOH terminus. A putative N-glycosylation sequence (Asn-Gly-Ser), three Arg-Gly-Asp triplets known as cell recognition peptides, frequent Lys residues in the Yaa position (which are templates for hydroxylation), several Lys-Gly-Asn/Xaa-Arg peptides known as the lysyl oxidase recognition site, and long stretches without imino acids could be found within the triple-helical domain. The short COOH-terminal noncollagenous domain closely resembles that of nematode cuticular collagens and vertebrate nonfibrillar collagens. Our results strongly support the idea that the diversity of collagen genes and gene families found in higher organisms already existed in sponge.